Commissioning of the Leksell Gamma Knife® Icon™. Issue 2 (30th January 2017) - Zeverino, Michele; Jaccard, Maud; Patin, David; Ryckx, Nick; Marguet, Maud; Tuleasca, Constantin; Schiappacasse, Luis; Bourhis, Jean; Levivier, Marc; Bochud, Francois O.; Moeckli, Raphaël
Abstract : Purpose: The Leksell Gamma Knife (LGK) Icon has been recently introduced to provide Gamma Knife technology with frameless stereotactic treatments which use an additional cone‐beam CT (CBCT) imaging system and a motion tracking system (IFMM, Intra‐Fraction Motion Management). The system was commissioned for the treatment unit itself as well as the imaging system. Methods: The LGK Icon was calibrated using an A1SL ionization chamber. EBT3 radiochromic films were employed to independently check the machine calibration, to measure the relative output factors (ROFs) and to collect dose distributions. Coincidence between CBCT isocenter and radiological focus was evaluated by means of EBT3 films. CBCT image quality was investigated in terms of spatial resolution, contrast‐to‐noise ratio (CNR), and uniformity for the two presets available (low dose and high dose). Computed Tomography Dose Index (CTDI) was also measured for both presets. Results: The absolute dose rate of the LGK Icon was 3.86 ± 0.09 Gy/min. This result was confirmed by EBT3 readings. ROF were found to be 0.887 ± 0.035 and 0.797 ± 0.032 for the 8 mm and 4 mm collimators, respectively, which are within 2% of the Monte Carlo‐derived ROF values. Excellent agreement was found between calculated and measured dose distribution with the gamma pass rate >95% of points for the nine dose distributions analyzed with 3%/1 mm criteria. CBCT isocenter was found to be within 0.2 mm with respect to radiological focus. Image quality parameters were found to be well within the manufacturer's specifications with the high‐dose preset being superior in terms of CNR and uniformity. CTDI values were 2.41 mGy and 6.32 mGy, i.e. −3.6% and 0.3% different from the nominal values for the low‐dose and high‐dose presets, respectively. Conclusions: The LGK Icon was successfully commissioned for clinical use. The use of the EBT3 to characterize the treatment unit was demonstrated to be feasible. The CBCT imaging system operates well within the manufacturer's specifications and provides good geometrical accuracy.